Can the WTO Survive and Perhaps Even Thrive During the Second Trump Term? A Hopeful Opinion - Kho, Stephen; Kirwin, Sarah; Laing, Sally (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2025)
The World Trade Organization (WTO), once a cornerstone of global trade, is now in serious longevity jeopardy, many exacerbated by the United States. Washington has imposed unilateral tariffs, withheld funding, and blocked Appellate Body appointments, leaving the dispute settlement system crippled. At the same time, multilateral negotiations have slowed to a trickle, as consensus among 166 sovereign Members has proven increasingly elusive. The very notion of trade as a “win-win” process is challenged, with Members exploiting exceptions in bad faith and treating trade as zero-sum. Yet, the article argues that the WTO can—and must—survive. To do so, it must demonstrate greater flexibility and pragmatism. Recent incremental achievements, like the Agreement on Trade Facilitation and the Fish Subsidies Agreement, show that progress, even if modest, is possible. The authors stress that clinging to mandatory consensus and the universal use of the most favored nation treatment prevents innovation. Alternatives such as plurilateral or sectoral “joint initiatives,” supported by the Secretariat, could allow willing members to move forward while others join later. Revitalizing dispute settlement is also critical. Some of the article’s proposals include faster timelines, limits on appeals, streamlined compliance proceedings, and a stronger appointment process to restore credibility. Ultimately, the central challenge is leadership: with the United States pulling back, the WTO needs new, diverse, and pragmatic leaders—whether among Members or within the Secretariat—to prioritize collective progress over narrow interests. Only then can the WTO move beyond paralysis and remain relevant in a changing world.